Analisis Pencegahan Kekerasan dan Pendekatan Adil Gender pada Sekolah Muhammadiyah Berbasis Pesantren di Jawa Timur: Analysis of Violence Prevention and Gender Equality Approach in Muhammadiyah Boarding School in East Java - Wahyuni, Holy Ichda; Budiman, Agus; Setiawan, Fajar (Anterior Jurnal, 2024)
Nowadays, it has become a trust issue, about violence and sexual harassment in the Islamic boarding school environment. In addition to parenting patterns, a gender-fair approach is also an aspect that needs to be studied. This study aims to analyze the prevention of violence and a gender-equality approach in Muhammadiyah boarding schools in East Java. This research is a qualitative study. The subjects of the study were selected using a purposive method, they are the chief and caregivers of the boarding school in two Islamic boarding schools located in Sidoarjo Regency and Lamongan Regency, East Java. The research data collection technique was carried out using 3 (three) methods, observation, documentation, and interviews. The data analysis technique used descriptive analysis. The study showed that in terms of preventing violence, Muhammadiyah Islamic boarding schools use a parenting pattern strategy that prioritizes child-friendly principles, and minimizes physical punishment, with the concept of rahmatan lil alamin. Meanwhile, in terms of preventing sexual abuse, education is considered less massive and has not touched on the substantive realm across genders. Furthermore, a gender-fair approach is shown by equality in access to opportunities for male and female students in organizational leadership, as well as in the practice of preaching.